Distributive trade in Malaysia: Emerging trends & challenges - Jaafar, Ahmad Sobri (2007)
Distributive trade is an important sub-sector of domestic trade. It is the third biggest contributor to GDP in 2005 and the second largest in terms of employment after manufacturing. Key drivers for growth in Malaysian distributive industry in particular retailing are increasing incomes and affluence, urbanization, changing consumer lifestyle and increased market liberalization. It is anticipated that retail trade will continue to be an important economic activity in the country in the future. The Malaysian distributive trade in particular retailing is confronting with increase competition with more players and expansion of foreign firms. To address this challenge the domestic distributive sector need to enhance it competitiveness. Local retailers and wholesalers must undertake efforts to strengthen their capacity and capability to respond to changes in the general tastes and preferences of consumers as well as increased competition in the marketplace. In terms of the government, effective measures need to be undertaken to strengthen the appropriate policy and legal framework to promote a competitive, efficient and dynamic domestic trade sector.